Investigation on the effect of shear connector in composite space structures - Lakshmikandhan, K.N.; Sivakumar, P.; Ravichandran, R.; Jayachandran, S. Arul; Senthil, R. (Journal of Structural Engineering, 2024)
Space structures are common in covering large area with few or no intermittent supports. The catastrophic failures of space structures are frequently reported and it urges to develop suitable techniques to prevent such failures. The composite space structures are found to be an efficient solution, in which the forces in the critical compression members are redistributed and safe guarded with concrete slabs. In this study, numerical studies were conducted using a standard finite element analysis package. Effect of shear connectors with varying heights on the behaviour of the space structure is studied. Results are compared with the steel space structure and composite space structure with full shear interaction. The maximum deflection observed in the steel space structure for the service load is less than span/300 and the maximum deflection observed in the steel concrete composite space structure for the service load is less than span/360, which ensures the serviceability conditions. The results show about 20 to 30 percent of reduction in deflection with about 250 percent increase in stiffness due to the composite action for the service load. The results substantiate that the length of shear connector should be equal to the concrete depth for more efficient composite interaction. The composite action is more effective and efficient in composite space structure for larger spans compared to shorter spans.